Supporters' attitudes towards European football governance: structural dimensions and sociodemographic patterns. (19th May 2021) - García, Borja; Llopis-Goig, Ramón
ABSTRACT: The role of fans in football governance is a topic of increasing academic and political interest. This article offers a quantitative approach to investigate supporters' opinions of governance structures in European football. It asks whether fans trust governing bodies, clubs, leagues and other stakeholders currently in charge of football governance. It also investigates the extent to which fans consider they should have a direct say on how football clubs are governed. Drawing on concepts from sports governance literature, an online survey collects opinions of football fans in six European countries (United Kingdom, Spain, Turkey, Poland, France, and Germany). The results indicate a high level of mistrust from the fans on national governing bodies and presidents and owners of football clubs. Supporters have a positive view of fan involvement in governance structures, but are pessimist about the actual efficacy of supporters' activism.